Catégories caduques. Au-delà de la distinction entre images artistiques et images scientifiques - Giuseppe Di Liberti; Andrea Pinotti (Images Re-Vues)
In the iconosphere we inhabit, are the categories of artistic image and scientific image still relevant? Perhaps we should think of them as operational, rather than ontological, categories, aimed at differentiating forms of thought, methods of interpretation or procedures of abstraction. Following such a differentiation, we could discover to what extent these forms are historically crossed and how today the interdisciplinary dialogue becomes a methodological imperative.